IMPROVING STUDENTS™ ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPH USING OUTLINE TECHNIQUE - Sabrina, Mutia -; Sianipar, Yunita Agnes (Universitas Negeri Medan, 2014)
Abstract This study deals with the improvement of the students™ achievement by using Outline technique. This research was conducted by applying classroom action research in two cycles. The subject of this research was one of a class in the first year student of SMU Yayasan Pendidikan Sultan Iskandar Muda. There were 35 students that participated in this research. The quantitative and qualitative data were gahtered in administrating writing test and diary notes. The result of quantitative data obtained that the score of the students inproved from cycle I to cycle II which the mean of the pre-test was 70.6, the test of cycle I was 75.8, and the test of cycle II was 85,2. The result of the quanlitative data described that the using of the Outline technique help to improve the students™ achievement in writing descriptive paragraph. Key Words : writing, writing achievement, paragraph, outline, references.